Evaluasi Sistem Proteksi Kebakaran Pada Gedung Sarana Edukasi SMP SMA Teuku Nyak Arif Fatih Bilingual School - Azkiyatul Faridy; Juliansyah Harahap; Marlisa Rahmi (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
Fire is a disaster that can occur in various places and times, either due to negligence, natural factors, or uncontrollable technical errors. This can certainly endanger and harm various parties. In an effort to reduce the impact of fire, the Government has issued regulations governing fire protection systems in buildings, according to the type and classification of buildings. This regulation is stated in the Regulation of the Minister of Public Works No. 26/PRT/M/2008 of 2008 concerning Technical Requirements for Fire Protection Systems in Buildings and the Environment.